An Iridium(III) Complex as a Photoactivatable Tool for Oxidation of Amyloidogenic Peptides with Subsequent Modulation of Peptide Aggregation. Issue 7 (3rd January 2017) - Kang, Juhye; Lee, Shin Jung C.; Nam, Jung Seung; Lee, Hyuck Jin; Kang, Myeong‐Gyun; Korshavn, Kyle J.; Kim, Hyun‐Tak; Cho, Jaeheung; Ramamoorthy, Ayyalusamy; Rhee, Hyun‐Woo; Kwon, Tae‐Hyuk; Lim, Mi Hee
Abstract: Aggregates of amyloidogenic peptides are involved in the pathogenesis of several degenerative disorders. Herein, an iridium(III) complex, Ir‐1, is reported as a chemical tool for oxidizing amyloidogenic peptides upon photoactivation and subsequently modulating their aggregation pathways.Ir‐1 was rationally designed based on multiple characteristics, including 1) photoproperties leading to excitation by low‐energy radiation; 2) generation of reactive oxygen species responsible for peptide oxidation upon photoactivation under mild conditions; and 3) relatively easy incorporation of a ligand on the Ir III center for specific interactions with amyloidogenic peptides. Biochemical and biophysical investigations illuminate that the oxidation of representative amyloidogenic peptides (i.e., amyloid‐β, α‐synuclein, and human islet amyloid polypeptide) is promoted by light‐activatedIr‐1, which alters the conformations and aggregation pathways of the peptides. Additionally, their potential oxidation sites are identified as methionine, histidine, or tyrosine residues. Overall, our studies onIr‐1 demonstrate the feasibility of devising metal complexes as chemical tools suitable for elucidating the nature of amyloidogenic peptides at the molecular level, as well as controlling their aggregation. Abstract : Oxidation at the flick of a switch : Oxidation of amyloidogenic peptides was achieved by an iridium(III) complex upon photoactivation under aerobic conditions, which subsequently enabled control of peptide aggregation pathways (see figure).